A Physiologically Responsive Nanocomposite Hydrogel for Treatment of Head and Neck Squamous Cell Carcinoma via Proteolysis‐Targeting Chimeras Enhanced Immunotherapy. Issue 12 (10th February 2023) - Wu, Yaping; Chang, Xiaowei; Yang, Guizhu; Chen, Li; Wu, Qi; Gao, Jiamin; Tian, Ran; Mu, Wenyun; Gooding, John Justin; Chen, Xin; Sun, Shuyang
Abstract: Although immunotherapy has revolutionized oncotherapy, only ≈15% of head and neck squamous cell carcinoma (HNSCC) patients benefit from the current therapies. An immunosuppressive tumor microenvironment (TME) and dysregulation of the polycomb ring finger oncogene BMI1 are potential reasons for the failure. Herein, to promote immunotherapeutic efficacy against HNSCC, an injectable nanocomposite hydrogel is developed with a polymer framework (PLGA‐PEG‐PLGA) that is loaded with both imiquimod encapsulated CaCO3 nanoparticles (RC) and cancer cell membrane (CCM)‐coated mesoporous silica nanoparticles containing a peptide‐based proteolysis‐targeting chimeras (PROTAC) for BMI1 and paclitaxel (PepM@PacC). Upon injection, this nanocomposite hydrogel undergoes in situ gelation, after which it degrades in the TME over time, releasing RC and PepM@PacC nanoparticles to respectively perform immunotherapy and chemotherapy. Specifically, the RC particles selectively manipulate tumor‐associated macrophages and dendritic cells to activate a T‐cell immune response, while CCM‐mediated homologous targeting and endocytosis delivers the PepM@PacC particles into cancer cells, where endogenous glutathione promotes disulfide bond cleavage to release the PROTAC peptide for BMI1 degradation and frees the paclitaxel from the particle pores to elicit apoptosis meanwhile enhance immunotherapy. Thus, the nanocomposite hydrogel, which is designed to exploit multiple known vulnerabilities of HNSCC, succeeds in suppressing both growth and metastasis of HNSCC. Abstract : A PP‐RC‐H hydrogel confers potent immuno‐ and bio‐chemotherapeutic effects against tumor growth and metastasis by exploiting multiple known vulnerabilities of head and neck squamous cell carcinoma (HNSCC). This synergistic strategy reverses the immunosuppressive microenvironment in tumor tissues for immunotherapy and also used a proteolysis‐targeting chimeras drug and paclitaxel to induce tumor apoptosis and suppression of immune escape to further promote the immunotherapy against HNSCC.